Esotericism in the Mirror of COVID-19: Gregorian Bivolaru, MISA, and the Pandemic - Introvigne, Massimo (The journal of CESNUR, 2020)
Despite the legal prosecution of its founder, Gregorian Bivolaru, the Movement for Spiritual Integration into the Absolute (MISA) remains one of the largest international spiritual movements based on esotericism. During the COVID-19 crisis, Bivolaru delivered several lectures on the epidemic. He contested the monopoly of science in offering answers to the crisis, and emphasized the importance of natural remedies, particularly phytotherapeutic, for an effective prophylaxis. Ultimately, however, he taught that an adequate response to COVID-19 should also rely on esoteric exercises based on meditation, blessings, and the use of mantras. The paper discusses MISA’s answer to COVID-19 within the framework of the existing literature on esotericism, healing, and science.